Associations of self-reported eating disorder behaviors and personality in a college-educated sample. (1st August 2020) - Calland, Alyssa R.; Siegler, Ilene C.; Costa, Paul T.; Ross, Leanna M.; Zucker, Nancy; French, Robin; Hauser, Elizabeth; Huffman, Kim M.
Abstract: Objective: In order to better understand factors motivating eating disorder (ED) behaviors and better identify persons at-risk for these behaviors, we sought to identify which personality domains and facets were associated with behaviors for weight control. Methods: ED behavior information was gathered from the University of North Carolina Alumni Heart Study using the question, "have you ever used any of the following to lose weight?" Respondents endorsed any combination of the following: "Vomiting, " "Fasting, " "Laxatives, " "Excessive physical exercise." Personality was measured using the Revised NEO Personality Inventory (NEO-PI-R). One-way ANOVAs were performed comparing personality domains and facets to reported ED behaviors, computed both as separate behaviors and the number of cumulative behaviors. Results: Of 3496 respondents, 9.41% endorsed ever having used at least one ED behavior, with the majority endorsing only a single ED behavior. For both sexes, endorsing greater numbers of ED behaviors was associated with higher scores on Neuroticism and Openness. For women, the strongest associations for behaviors with personality were: excessive exercise with high Impulsiveness; fasting with high Impulsiveness and low Gregariousness; laxative use/purging with high scores on Activity and Feelings. For men, the strongest associations were: excessive exercise with high Impulsiveness; fasting with high Ideas; laxative use/purging with low Modesty. Discussion: Data collected from this sample showed a sex-modulated pattern of association between personality domains and facets with ED behaviors. Our findings support that obtaining personality profiles of individuals exhibiting subclinical eating behaviors will enhance our understanding of who is at risk of developing an ED diagnosis.